GE_GERICHTE P/22456/2019 vom 20. Dezember 2024 - GE Cour de justice (2024)
BRIGANDAGE;MENACE(DROIT PÉNAL);CONTRAINTE(DROIT PÉNAL);VIOLATION D'UNE OBLIGATION D'ENTRETIEN;VIOLATION DU DEVOIR D'ASSISTANCE OU D'ÉDUCATION;CONFRONTATION | CP.181; CP.180; CP.140; CP.217; CP.219; CPP.147.al1